3D FEM validation of ultra-small inner spiral ribbed copper tube using the tube sinking method. Issue 9 (December 2015) - Tangsri, Tanit; Norasethasopon, Somchai
Abstract This research related to the development of ultra-small inner spiral ribbed copper tubes (ISRCTs) which have high quality and efficiency in transferring heat. The deformation behaviour of the ISRCT was studied. Three-dimensional finite element models were constructed for the various process parameters: the change of the cross-section profiles of the ribbed contours and the spiral angle of the ribbed area of the ISRCT, for twelve multi-pass drawings through the die using the tube sinking method. The effect of the ribbed spiral angle and the ribbed cross-sectional profile was also studied. Modelling and simulation techniques were performed using commercial Abaqus software to learn whether the surface profiles of the ISRCT increased or reduced with tube sinking using the finite element method (FEM). Results of the multi-pass drawing analysis were summarised and compared to the experimental findings. The FEM simulation approach was used to analyse the changes of ten parameters: von Mises stress, wall thickness, ribbed base width, ribbed tip width, ribbed base gap, ribbed tip gap, ribbed height, ribbed pitch, axial displacement and ribbed spiral angle. This procedure can be used to improve product quality and to study the effect of the various parameters. The results will be very valuable for researchers and well engineers for future design of ultra-small ISRCT to improve the quality and efficiency of heat transfer.